Connectedness and spillovers between African and global Islamic equities: implications for portfolio hedging and investment strategies - Andrew Phiri; Izunna Anyikwa (Cogent Economics & Finance)
Despite the surge in interest of international investors in African and Islamic equities as portfolio diversifiers of international equities, surprisingly, little attention has been paid to the diversifying properties of these stocks against each other. Thus, we examine the spillover and connectedness effects between conventional African and global Islamic equities using the time-varying parameter (TVP-VAR) connectedness approach applied to daily time series spanning 16/05/2013 to 28/02/2024. We also adopted the minimum connectedness portfolio (MCoP) approach to extract multivariate and bivariate optimal portfolio weights for different combinations of African and Islamic equities. We find that the transmission effects of systemic shocks from Islamic markets to African markets are more prominent for Egyptian equities that are Sharia-compliant. Furthermore, larger, non-Sharia-compliant African markets such as South Africa and its closely integrated allies, namely Namibia and Botswana, are responsible for systemic shocks to other African markets. Lastly, larger African markets, such as Egypt, South Africa, and Namibia, improve the hedging effectiveness of multivariate optimum portfolios, whereas Islamic equities are more suitable for enhancing the hedging effectiveness of pairwise portfolio combinations with African equities. The investor and policy implications of these findings are further discussed.